2020
DOI: 10.1093/eurheartj/ehaa770
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1): a crucial driver of atherosclerotic cardiovascular disease

Abstract: Cardiovascular diseases (CVDs), specifically lipid-driven atherosclerotic CVDs, remain the number one cause of death worldwide. The lectin-like oxidized low-density lipoprotein (LDL) receptor-1 (LOX-1), a scavenger receptor that promotes endothelial dysfunction by inducing pro-atherogenic signalling and plaque formation via the endothelial uptake of oxidized LDL (oxLDL) and electronegative LDL, contributes to the initiation, progression, and destabilization of atheromatous plaques, eventually leading to the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 118 publications
0
55
0
Order By: Relevance
“…Endothelial cells adhere to circulating leukocytes via vascular cell adhesion molecule-1 (VCAM-1) on their cell surface [ 65 ]. Endothelial cells assimilate oxidized LDL via low-density lipoprotein receptor-1 (LOX-1), which is conducive to the development of atherosclerotic plaques [ 66 ]. Many studies have reported the relationship between endothelial dysfunction and coronary disease.…”
Section: Mechanism Of Action Of Colchicine In Cardiovascular Disease Preventionmentioning
confidence: 99%
“…Endothelial cells adhere to circulating leukocytes via vascular cell adhesion molecule-1 (VCAM-1) on their cell surface [ 65 ]. Endothelial cells assimilate oxidized LDL via low-density lipoprotein receptor-1 (LOX-1), which is conducive to the development of atherosclerotic plaques [ 66 ]. Many studies have reported the relationship between endothelial dysfunction and coronary disease.…”
Section: Mechanism Of Action Of Colchicine In Cardiovascular Disease Preventionmentioning
confidence: 99%
“…The analysis revealed also that SR-BI correlates with one more parameter -Lectin-type oxidized LDL receptor 1 (LOX-1). In the latest publications (2020 and 2021), LOX-1 is presented as a promising target for early diagnosis and cardiovascular risk prediction [39][40][41]. Such enthusiastic announcements made us expect to nd higher levels of LOX-1 in people with stroke, after a myocardial infarction or with obesity, but no such association was found in our geriatric population.…”
Section: Discussionmentioning
confidence: 93%
“…The ox-LDL/LOX-1 complex causes the following impacts: increasing ROS production, death of SMCs, MMP influence on a fibrous cap, providing a route of entry for ox-LDL into endothelium, disrupting the normal endothelial function and monocyte adhesion, and infiltration. The stimulation of LOX-1 causes endothelial dysfunction, leukocyte adhesion, collagen degradation, and foam cell formation ( 64 ). Lp-PLA2 has performed its proinflammatory and proatherogenic functions by promoting monocyte chemotaxis, enhancing expression of mononuclear leukocyte adhesion molecules in endothelial cells, producing lysophosphatidylcholine (lysoPC) and non-esterified fatty acid moieties ( 9 ).…”
Section: Resultsmentioning
confidence: 99%